Enhancing theranostic potential of anti-mesothelin sdAb through site-specific labeling at a unique conserved lysine by molecular engineering - Émilien N’Guessan; Florian Raes; Mitra Ahmadi; Sandrine Bacot; Laurent Dumas; Julien Leenhardt; Marlène Debiossat; Clémence André; Jean-Luc Lenormand; Catherine Ghezzi; Daniel Fagret; Charlotte Lombardi; et al. (EJNMMI Radiopharmacy and Chemistry)
Abstract Background Mesothelin is a 40 kDa glycoprotein overexpressed in several cancers, including triple-negative breast cancer (TNBC). The anti-mesothelin single-domain antibody (sdAb, or nanobody) A1 can serve as a radio-theranostic agent, but random DOTA conjugation on lysines yields heterogeneous products. Results We reengineered A1-His by directed mutagenesis to produce four single-lysine variants (A1K1-His, A1K2-His, A1K3-His, and A1K4-His). Each was site-specifically conjugated with p-SCN-Bn-DOTA, radiolabeled with 68Ga, and evaluated by PET imaging in mice bearing HCC70 TNBC xenografts, followed by ex vivo biodistribution at 1 h post-injection. All mutants were successfully produced and site-specifically conjugated. A1K1-His showed lower conjugation efficiency and increased liver/spleen retention, whereas A1K3-His exhibited reduced stability. A1K2-His and A1K4-His performed best overall. Removing the His-tag and administering gelofusin further lowered renal uptake. Notably, A1K2 displayed tumor-to-kidney and tumor-to-liver ratios 2.4 and 1.9 times higher, respectively, than A1K4 (p < 0.01). Conclusions For the first time, site-specific DOTA conjugation using sdAb derivatives containing a single lysine was achieved, avoiding the production of mixed final compounds. These findings identify 68Ga-DOTA-A1K2 as the leading candidate for mesothelin-expressing tumor imaging with minimal off-target uptake. Ongoing studies will assess its therapeutic utility with 177Lu-DOTA-A1K2. Since these four lysines are conserved in many sdAbs, this strategy may be broadly applicable for site-specific sdAb labeling.